Synthesis of benzylidene-benzofuranone derivatives as probes for detection of amyloid fibrils in cells - Tavakoli, Mohsen; Ghadami, Seyyed Abolghasem; Adibi, Hadi; Gulcan, Hayrettin Ozan (Taylor & Francis Inc, 2023)
Aggregated protein is the common cause of a wide variety of neurodegenerative diseases, such as Alzheimer's disease (AD), Parkinson's disease, etc. It is proven that protein aggregation like amyloid beta (A beta) is one of the critical factors causing AD and, its diagnosis in the early stages of the disease is important for the treatment or prevention of AD. To have a better understanding of protein aggregation and its pathologies, there is a huge need to design and develop new and more trustworthy probe molecules for in vitro amyloid quantification and in vivo amyloid imaging. In this study, 17 new biomarker compounds, have been synthesized from benzofuranone derivatives, to detect and identify amyloid in vitro (dye-binding assay) as well as in the cell by staining method. According to the results, some of these synthetic derivatives can be considered suitable identifiers and quantifiers to detect amyloid fibrils in vitro. Compared to thioflavin T, 4 probes out of 17 probes have shown good results in selectivity and detectability of A beta depositions, and their binding properties were also confirmed with in silico analysis. The drug-likeness prediction results for selected compounds by the Swiss ADME server show a satisfactory percentage of blood-brain barrier (BBB) permeability and gastrointestinal (GI) absorption. Among all of them, compound 10 was able to show better binding properties than others, and in vivo study showed that this compound was capable of detecting intracellular amyloid.Communicated by Ramaswamy H. Sarma
Keywords: Neurodegenerative diseases; Amyloid beta; Insulin; Benzylidene derivatives; Benzofuranone derivatives